From Memory to Marble The Historical Frieze of the Voortrekker Monument, Part I: The Frieze - Rankin, Elizabeth (African Minds, 2020)
The pictorial narrative of the Boer pioneers who conquered South Africa's interior during the 'Great Trek' (1835-52) represents a crucial period of South Africa's past. Forming the concept of the frieze both reflected on and contributed to the country's socio-political debates in the 1930s and 1940s when it was made. The frieze is unique in that it provides rare evidence of the complex processes followed in creating a major monument. Based on unpublished documents, drawings and models, these processes are unfolded step by step, from the earliest discussions of the purpose and content of the frieze through all the stages of its design to its shipping to post-war Italy to be copied into marble and final installation in the Monument. The book examines how visual representation transforms historical memory in what it chooses to recount, and the forms in which it depicts this. It also investigates the active role the Monument played in the development of apartheid, and its place in post-apartheid heritage.